Aesthetic Musicality of Arthur Schopenhauer and New Testament Throughout the Ages: Musikalitas Estetis Arthur Schopenhauer dan Perjanjian Baru Sepanjang Zaman - Munte, Alfonso; Natalia, Destri; Magdalena, Elsa; Wijaya , Nicolhas Jurdy; Malau, Reynhard (Journal of Social and Humanities, 2023)
Based on the qualitative research, data seeking technique was applied through literature reviews. Literature studies used secondary sources or previous research from researchers associated with music, aesthetics, and the New Testament. The previous studies showed a diversity of views which led to aesthetic participation of music in melodies, rhythms and tempos in an axiological sense and musical aesthetics as a depiction of feelings, struggles (parents, children, [female] activists), and manuscript excavation tools throughout the ages. These tools of aesthetics are fused with the thoughts of philosopher Arthur Schopenhauer who spoke of aesthetics, desire and ideas. The intention of our research is to demonstrate the network of previous researches as an intertwined encounter with one another to counter the aesthetic ultimacy that considers one aesthetic preferable to another in music and even in the New Testament. The research results reveal the existence of a space of togetherness between aesthetic diversity in and through music as a dynamic tension through the insight of Arthur Schopenhauer.